Could Some Geriatric Characteristics Hinder the Prescription of Anticoagulants in Atrial Fibrillation in the Elderly? - Paule Denoël; Jacques Vanderstraeten; Pierre Mols; Thierry Pepersack (Journal of Aging Research)
Several studies have reported underprescription of anticoagulants in atrial fibrillation (AF). We conducted an observational study on 142 out of a total of 995 consecutive ≥75 years old patients presenting AF (14%) when admitted in an emergency unit of a general hospital, in search of geriatric characteristics that might be associated with the underprescription of anticoagulation therapy (mostly antivitamin K at the time of the study). The following data was collected from patients presenting AF: medical history including treatment and comorbidities, CHADS2 score, ISAR scale (frailty), Lawton’s scale (ADL), GDS scale (mood status), MUST (nutrition), and blood analysis (INR, kidney function, and albumin). Among those patients for who anticoagulation treatment was recommended (73%), only 61% were treated with it. In the group with anticoagulation therapy, the following characteristics were observed more often than in the group without such therapy: a recent (≤6 months) hospitalization and medical treatment including digoxin or based on >3 different drugs. Neither the value of the CHADS2 score, nor the geriatric characteristics could be correlated with the presence or the absence of an anticoagulation therapy. More research is thus required to identify and clarify the relative importance of patient-, physician-, and health care system-related hurdles for the prescription of oral anticoagulation therapy in older patients with AF.